The use of polyethylene glycol as a maintenance treatment of functional constipation in children living in Egypt - Olivia Kameel Shokrey Bastaoros; Mostafa Ahmed Gad; Ayman Emil Eskander; Mourad Alfy Ramzy; Amera Hasnoon (SpringerOpen, 2023)
Abstract Background Constipation is an underestimated but common health problem worldwide, decreasing the quality of life. Functional constipation (FC) is a common pediatric problem, with reported prevalence ranging from 0.7 to 29.6%. In Egypt, there are no established guidelines for the treatment of constipation in children. Objectives The aim of this study was to investigate the efficacy of polyethylene glycol (PEG) as a maintenance treatment for functional constipation (FC) in comparison with the classic treatment using (lactulose and senna) in children living in Egypt. Patients and method This is a randomized single-blinded clinical trial study on pediatric patients who presented with functional constipation at the outpatient clinic of Cairo University Specialized Pediatric Hospital. The study was conducted on 80 children with functional constipation, who were divided into 2 groups: group 1 (40 children), who received polyethylene glycol as maintenance treatment; group 2 (40 children), who received classic treatment in the form of osmotic laxative (lactulose) with or without stimulant (senna-sennosides or senna-glycoside) according to the stool consistency. Results Our data showed significant improvement in the fecal masses and the number of defecation, fecal pseudo incontinence, painful or hard bowel movement, history of retentive posturing or excessive violation, and large fecal masses in the rectum between group 1 and group 2 after treatment. In group 1, there was a significant improvement in anthropometric measures, CBC parameters, abdominal circumference, and anal fissures and piles after treatment; also, there was a significant decrease in the number of patients that need to continue treatment in group 1 in comparison with group 2 and number of patients that had impaction during treatment. However, there was a statistically significant increase in the number of patients who complained of palatability in group 1. Conclusion PEG has long-term efficacy in the management of pediatric functional constipation. Significant improvement of results in comparison with the classic treatment (lactulose or senna-lax).